Nonlinear dynamic measurement of self-sustained thermoacoustic oscillations in a swirling combustor with a heat exchanger - Zhang, Zhiguo (2018)
Energy transfer from heat to sound is unwanted in many propulsion systems, including gas turbines and rocket motors. However, it is favorable in some practical applications, such as thermoacoustic heat engines or cooling systems. The present work considers an experimental investigation of self-sustained thermoacoustic oscillations in a swirling combustor. Both subcritical and supercritical Hopf bifurcations are found to occur in this swirling combustor. In the presence of the subcritical bifurcation, a small change in the equivalent ratio leads to a sudden/hard jump from steady state to large amplitude limit cycle oscillations. The experimental study sheds lights on the heat-to-sound conversion process. In addition to increase the heat-to-sound energy conversion, an innovative water-involved heat exchanger is designed and experimentally implemented on the swirling combustor. By doing this, self-excited thermoacoustic oscillations are found to be intensified. The present work opens up a new applicable way to amplify thermoacoustic oscillations in swirling combustion systems.